Patient with constipation syndrome at the ambulatory-polyclinic reception: actual aspects of diagnosis and treatment - E. N. Degovtsov; D. I. Trukhan; V. A. Nikonenko; V. K. Kosenok (Амбулаторная хирургия)
An actual problem in surgical practice is paresis of the gastrointestinal tract, the main manifestation of which is constipation after surgical treatment. Treatment of postoperative gastrointestinal paresis, which is manifested primarily by constipation, should be comprehensive and, if necessary, patients are shown taking laxatives to stimulate bowel function.Sodium picosulfate is one of the most commonly used and effective drugs, belongs to the group of synthetic stimulant laxatives. The above review noted the safety and effectiveness of sodium picosulfate for atonic constipation, for regulating stool (hemorrhoids, proctitis, anus cracks), for preparing for surgical operations, instrumental and radiological examinations.The presence of picosulfate in the clinic and hospital surgeon’s arsenal makes it possible to optimize the drug therapy in surgical patients with constipation syndrome at the hospital and outpatient treatment stage.